Cumulative risk, teacher-child closeness, executive function and early academic skills in kindergarten children. (February 2020) - Suntheimer, Noelle M.; Wolf, Sharon
Abstract: We tested the role of teacher-child closeness in moderating the associations between early childhood adversity, measured as a cumulative risk index, and child outcomes during the kindergarten year. Using the ECLSK:11, a national dataset of kindergarteners in the 2010–11 academic year, we examined three dimensions of executive function (cognitive flexibility, inhibitory control, working memory), as well as early reading and math scores, as key skills that facilitate the transition to school. Cumulative risk was negatively associated with all outcomes, and teacher-child closeness was positively associated with all outcomes. Teacher-child closeness moderated the relation between cumulative risk and working memory and cumulative risk and reading scores in a protective manner, but not cognitive flexibility, inhibitory control, or math scores. Implications for research in early childhood adversity and education are discussed.